Knowledge of Pakistani Nurses about Theory Practice Gap in Nursing - Alina Hameed, Kabir Ozigi Abdullahi, Adnan Yaqoob, (Pakistan Journal of Medical & Health Sciences, 2023)
Aims: To evaluate the knowledge of the participants about theory practice gap and to determine the association of knowledge with demographic variable like age and educational level of the participants. Methodology: A cross sectional study design was used to conduct this study. This study was conducted at Government and private Universalities or Hospitals Lahore. Approximately 09 months after the approval of synopsis from Research Ethical Committee (REC). Sample size of 192 cases is calculated with 95% confidence interval, 7% margin of error and convenient sampling was used. Target population of the present study was nursing instructors and clinical nurses. SPSS version 21.0 was used for data analysis. Quantitative variables mean and standard deviation was be used. For categorical variables frequency and percentage was used.Chi-square test was be used. P-Value 0.05 was being considered statistically significant. The study was conducted in private and public sector in Lahore. Results: In out of 192 respondent about 65.63% having score less than 13.8 and 34.38% scored between 13.8-18.4. However non of the participents have score greater than > 18.4. Its mean that most of the study particepents fall in the poor knoweledge score. It further illustrated that regarding to assess the knowledge level of the participents about theory practice gap; show that there were no awearness regarding the thory practice gap in nursing. The finding of this study as helpful for the future researcher and educational institute how to reduce this theroy prectice gap. Conclusion: It is not enough to have good knowledge about the existence of the gap; efforts must be made to minimize it in order to close the theory-practice gap. The theory-practice gap can be reduced or minimized through effective collaboration, improved knowledge acquisition, continuous education, periodic curriculum updates, and the incorporation of evidence-based practices into the curriculum of learning. Keywords: Theory-Practice Gap, Knowledge, Pakistani Nurse, Educators, Private and Government Institute